PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. TOTAL CIPTA SOLUSINDO - Nazilah Nur Hidayah (Jurnal Menara, 2024)
The purpose of this research is to find out whether work discipline and work environment influence employee performance at PT. Total Cipta Solusindo. The method used is a quantitative method. Using a saturated sampling technique with a sample of 44 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The results of this research are that work discipline influences employee performance with the regression equation Y = 22.462 + 0.380X₁, a correlation coefficient of 0.400, meaning that the two variables have a moderate level of relationship. Hypothesis testing obtained t count > t table or (2.827 > 2.018) thus H₀ is rejected and H₁ is accepted, meaning that there is a partially significant influence between work discipline on employee performance at PT Total Cipta Solusindo. Hypothesis testing obtained t count > t table or (4.691 > 2.018) thus H₀ is rejected and H₂ is accepted. Hypothesis testing obtained a calculated F value > F table or (22.002) > 2.830), thus H₀ was rejected and H₃ was accepted. This means that there is a significant influence simultaneously on work discipline and work environment on employee performance at PT Total Cipta Solusindo.